PENGARUH TINGKAT PENDIDIKAN ORANG TUA DAN FASILITAS BELAJAR TERHADAP PRESTASI BELAJAR SISWA KELAS XI IPS SMA NEGERI 2 TAMBANG KABUPATEN KAMPAR - Siti Khadijah Khadijah; Suarman '; Henny Indrawati Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aimed to determine the effect of parental education and learning facilities on student achievement in class XI IPS SMAN 2 Tambang Kabupaten Kampar. This research was conducted at SMAN 2 Tambang of the month December 2014 to February 2015. The research method used is descriptive quantitative method. A population of 121 students and all the sampled population (census). Data collection instrument used was a questionnaire using a Likert scale for the independent variables: education level of parents (X1) and learning facilities (X2). The data analysis technique used is multiple linear regression. The result showed that the level of parental education and learning facilities simultaneously influence on student achievement. It is based on the results of analyzes, calculations show of F > F table (5.515 > 2.696). While partially levels of parental education and learning facilities effect on student achievement in class XI IPS SMAN 2 Tambang. This is evidenced by the t test, parental education level variables obtained t value 2.291 dengan 2,319 t tabel 1,660 and learning facilities with ttabel 1,660 value. So it can be concluded that the level of parental education and learning facilities effect on student achievement with a contribution of 85.5% and the remaining 14.5% is influenced by other factors not examined as the school environment, society, and so forth.   Keywords : influence, parental education levels, facilities, academic achievement